World Equilibrium Distortions And The House Of Cards Effect: A Scientific Analysis Of Systemic Vulnerabilities And Global Disequilibria - Shubhada Subhash Patil (IJRDO - Journal of Business Management, 2025)
This paper presents a unified macroeconomic disequilibrium framework wherein global economic saturation, yield curve dislocations, monetary policy nonlinearity, and equilibrium data opacity coalesce to generate systemic financial entropy—manifesting as the House of Cards Effect. By modeling the global economy as a multidimensional field of synchronously calibrated macro-ratios, the study demonstrates how fractional deviations in apex bank signaling—especially in the form of distorted term structures and misaligned real yield spreads—propagate algorithmic mispricing, disrupt monetary transmission channels, and lead to sovereign liquidity crises. Employing a scientific paradigm that parallels atomic destabilization and quantum decoherence, this thesis constructs a rigorous analogy between financial equilibrium loss and molecular symmetry collapse. The empirical substrate of the study triangulates anomalies in the U.S. Federal Reserve’s policy inertia, the European Central Bank’s artificial currency inflexion, China’s yield management-induced opacity, and Russia’s externally induced credit implosion. These disruptions are modeled as interdependent chain reactions in a complex system with vanishing policy elasticity. The study introduces the Equilibrium Ratio Saturation Theorem (ERST), positing that beyond a critical threshold of macro-ratio misalignment, traditional fiscal and monetary levers fail to exert causal influence on real sector variables. This condition renders central banks functionally inert, while endogenous policy loops amplify entropy across trade, capital, and monetary domains. The study concludes that the contemporary global economic order has reached a singularity of disequilibrium wherein conventional macroeconomic axioms no longer yield predictive or corrective power, necessitating a paradigmatic reassessment of systemic risk modeling and institutional policy design.